The Breakup and Dispersion of a New Conceptual "Continent" - Stewart, John; Hagstorm, Warren; Small, Henry (Geoscience Canada, 1981)
Abstract The recently developed technique of 'co-citation analysis' is used to examine intel-lectual developments in the geosciencesfrom 1970 to 1975. The results for 1970show a cluster of plate tectonics articlesthat are often cited together, and a 'pic-ture' of these articles and their interrela-tionships is presented as a series ofinterconnected hills - one hill for eacharticle. Results for 1973 and 1975 indicatethe rise of new clusters of articles asso-ciated with new research interests, e.g.,'hot spots', and the dispersion of the orig-inal cluster of plate tectonics as this the-ory was applied to other areas, e.g., con-tinental geology. These results arepresented so that geoscientists canassess the ability of this new technique toidentify changing theoretical interests inscience.